[PP.24.03] SATISFACTION WITH DABIGATRAN COMPARED WITH VITAMIN K ANTAGONISTS IN OUTPATIENTS WITH NONVALVULAR ATRIAL FIBRILLATION DAILY ATTENDED BY CARDIOLOGISTS. (September 2017) - Escobar, C.; Barrios, V.; Baron, G.; Doblas, Jj. Gomez; Parici, M.; Recalde, E.; Toril, J.; Chopo, J.M.; Rossi, P.; MonzerKhanji, M.
Abstract : Objective: To compare the quality of life of outpatients with nonvalvular atrial fibrillation (NVAF) daily attended by cardiologists treated with dabigatran or vitamin K antagonists (VKA). Design and method: This is an ongoing observational, prospective and multicenter study in which outpatients with NVAF daily attended by cardiologists in Spain that have started treatment with dabigatran or VKA in the last month are being included. All patients will be followed during 6 months. Quality of life and the perception of cardiologists about the satisfaction of patients with anticoagulant treatment will be analyzed. In this abstract, baseline data about the first 649 patients have been presented. Results: Mean age of patients was 73.5 ± 95 years, and 56.4% of patients were men. Mean CHA2-DS2-VASc score was 3.6 ± 1.5 and mean HAS-BLED score 1.4 ± 1.1. Permanent AF was reported in 41.4% of patients, paroxysmal AF in 33.1% of patients and persistent AF in 24.5% of patients. Data regarding the perception of cardiologists about the satisfaction of patients with treatment were reported in the table (from 0 [completely unsatisfied] to 10 [completely satisfied]). Figure. No caption available. Conclusions: In outpatients with NVAF daily attended by cardiologists, the perception of physicians about the efficacy, safety and satisfaction of patients with anticoagulant treatment was significantly better with dabigatran than with VKA.